Failure as adversity and the expansion of undergraduate in nursing: a qualitative study with Workers-Students - S. R. O. Maier; T. S. Santos; W. W. R. Souza (Scientific Electronic Archives, 2014)
<!--[if gte mso 9]> <![endif]--> <!--[if gte mso 9]> <![endif]--> Demonstrate the existence of failure in the academic route of Workers-students the undergraduate nursing UFMT-Sinop and how these students understand this process and what the causal factors of reprobation mentioned by students working.It was made a camp research with workers-students, nursing graduating and nursing technical in the city health system by Sinop, based on a semi-structured whose the answers it was analyzed through interview. The results were that the reprobation between workers-students is something present, primarily, the retentions in the basics formation discipline, according to the curriculum in effect. Thus the reprobation is something present on the academic trajectory of the workers-students, being the difficulty in reconciling work and academic activities an important and considerable causal factor to the working student can reach yours academics objectives.